GOVERNANCE AND FOREIGN DIRECT INVESTMENT : EVIDENCE IN ASEAN - Sakinah, Ramadhanti Dara; Firmansyah, Firmansyah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research analyzes the connection of Regulatory Quality (RQ) and Rule of Law (ROL) on Foreign Direct Investment (FDI) in ASEAN countries between 2002 to 2022. Utilizing the pooled mean group (PMG) technique with data sourced from the World Bank, the study found that Regulatory Quality significantly impacts FDI in the long term. Short-term results indicate significant corrections to the divergence of the long-term equilibrium production levels. Causality tests reveal a two-way relationship between FDI and Regulatory Quality in ASEAN countries, but no reciprocal relationship with Rule of Law was identified.